Carboplatin in BRCA1/2-mutated and triple-negative breast cancer BRCAness subgroups: the TNT Trial. (May 2018) - Tutt, Andrew; Tovey, Holly; Cheang, Maggie; Kernaghan, Sarah; Kilburn, Lucy; Gazinska, Patrycja; Owen, Julie; Abraham, Jacinta; Barrett, Sophie; Barrett-Lee, Peter; Brown, Robert; Chan, Stephen; et al.
Abstract Germline mutations inBRCA1/2 predispose individuals to breast cancer (termed germline-mutatedBRCA1/2 breast cancer, gBRCA-BC) by impairing homologous recombination (HR) and causing genomic instability. HR also repairs DNA lesions caused by platinum agents and PARP inhibitors. Triple-negative breast cancers (TNBCs) harbor subpopulations withBRCA1/2 mutations, hypothesized to be especially platinum-sensitive. Cancers in putative 'BRCAness' subgroups—tumors withBRCA1 methylation; low levels ofBRCA1 mRNA (BRCA1 mRNA-low); or mutational signatures for HR deficiency and those with basal phenotypes—may also be sensitive to platinum. We assessed the efficacy of carboplatin and another mechanistically distinct therapy, docetaxel, in a phase 3 trial in subjects with unselected advanced TNBC. A prespecified protocol enabled biomarker–treatment interaction analyses in gBRCA-BC and BRCAness subgroups. The primary endpoint was objective response rate (ORR). In the unselected population (376 subjects; 188 carboplatin, 188 docetaxel), carboplatin was not more active than docetaxel (ORR, 31.4% versus 34.0%, respectively;P = 0.66). In contrast, in subjects with gBRCA-BC, carboplatin had double the ORR of docetaxel (68% versus 33%, respectively; biomarker, treatment interaction P = 0.01). Such benefit was not observed for subjects withBRCA1 methylation, BRCA1 mRNA-low tumors or a high score in a Myriad HRD assay. Significant interaction between treatment and the basal-like subtype was driven by high docetaxel response in the nonbasal subgroup. We conclude that patients with advanced TNBC benefit from characterization ofBRCA1/2 mutations, but notBRCA1 methylation or Myriad HRD analyses, to inform choices on platinum-based chemotherapy. Additionally, gene expression analysis of basal-like cancers may also influence treatment selection. The phase 3 TNT Trial in subjects with triple-negative breast cancer supports the superiority of carboplatin over docetaxel inBRCA1/2 -mutated tumors and a greater response to taxanes in the nonbasal subtype.